2002
DOI: 10.1007/s00737-002-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression: prevalence and determinants in Lebanon

Abstract: This study assesses the prevalence and determinants of postpartum depression (PPD). 396 women delivering in Beirut and a rural area (Beka'a Valley) were interviewed 24 hours and 3-5 months after delivery. During the latter visit, they were screened using the Edinburgh postnatal depression scale. The overall prevalence of PPD was 21% but was significantly lower in Beirut than the Beka'a Valley (16% vs. 26%). Lack of social support and prenatal depression were significantly associated with PPD in both areas, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
170
12
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(210 citation statements)
references
References 38 publications
26
170
12
2
Order By: Relevance
“…These risk factors are likely to be interactive as well as multiplicative in effect. These findings are consistent with findings of previous studies such as poverty, [9] low level of education [14], more than one girl child [11], pressure and desire for a male child, high adverse life events score [8], previous psychiatric disorder [15], poor spousal relation [16], and poor support from the family [8] have been implicated as risk factors, although few studies have denied one or more of these factors as significant factors [17]. The study conducted in Chennai also indicated that PPD was significantly more in women who had unskilled husbands and had nonarranged marriages.…”
Section: Discussionsupporting
confidence: 91%
“…These risk factors are likely to be interactive as well as multiplicative in effect. These findings are consistent with findings of previous studies such as poverty, [9] low level of education [14], more than one girl child [11], pressure and desire for a male child, high adverse life events score [8], previous psychiatric disorder [15], poor spousal relation [16], and poor support from the family [8] have been implicated as risk factors, although few studies have denied one or more of these factors as significant factors [17]. The study conducted in Chennai also indicated that PPD was significantly more in women who had unskilled husbands and had nonarranged marriages.…”
Section: Discussionsupporting
confidence: 91%
“…Depressive mothers reported a history of psychiatric illness during pregnancy (Abou-Saleh & Ghubash, 1997;Chaaya et al, 2002;Eilat-Tsanani et al, 2006;Hamdan & Tamim, 2011;Inandia et al, 2002;Kheirabadi et al, 2009;Mohamed et al, 2011). Kheirabadi et al (2009) reported a 35.8% prevalence rate of severe depression (based on BDI score) in women with a previous history of depression.…”
Section: Physical/biological Factorsmentioning
confidence: 99%
“…This is consistent with a review of the literature conducted by Alici-Evcimen and Sudak (2003) in the United States. In addition, a history of chronic health problems and a lack of antenatal care are reported (Chaaya et al, 2002;Eilat-Tsanani et al, 2006;Glasser et al 2011;Rizk et al, 2005). In a study on PPD, Jordanian women also indicated that PPD had a negative physical effect on them (Khalaf, Abu-Moghli, Mahadeen, Callister, & Al-Hadidi, 2007) and presented somatic symptoms including backache, headache, and fatigue as major complaints (Rouhi, Usefi, & Mohamad Alizade, 2009).…”
Section: Physical/biological Factorsmentioning
confidence: 99%
“…Results in these studies showed that childbirth with C-section surgery increased the possibility of depression. While results of study by Chaaya et al (57) showed that depression is lower among mothers with C-section surgery than mothers with natural childbirth. Carter et al (58) also investigated the results of depression and postpartum depression reported in 24 studies; there was a relationship between these two factors in 5 articles, while in 15 studies, no relationship was observed between the two factors.…”
Section: Discussionmentioning
confidence: 90%